Microstructure and Giant Dielectric Permittivity of Titano-Manganite Systems - Primus, Walter Charles (2008)
The microstructural and dielectric properties of La0.4Ba0.6-xCaxMn0.4Ti0.6-ySnyO3 (x = 0.0, 0.2, 0.4, 0.6; 0.0 ≤ y ≤ 0.6) ceramic systems have been investigated. The samples were prepared using solid-state technique where calcinations was done at 950 °C for 24 hours and sintered at 1300 °C for 3 hours after three times heating of 72 hours at 1300 °C. Surface morphology study showed a well define grain and grain boundary and no changes in grain size when Ba ions substituted with Ca ions. However, the grains size becomes smaller from ~ 7 μm to ~ 1.5 μm as Sn ions were introduced into the Ti site of titano-manganite samples. At high Sn concentrations, the grain boundaries become smeared. The atomic percentage obtained from EDX analysis shows small deficits ± 0.05 with the calculated percentage. In XRD analysis, the La0.4Ba0.6-xCaxMn0.4Ti0.6O3 samples with x = 0.0 and 0.2 are cubic structure (Pm-3m) and distorted to a tetragonal structure (I4mcm) as the composition of x = 0.4 and 0.6. Substituted Ti ions with Sn ions cause the samples structure change from tetragonal to orthorhombic (Pnma). A huge dielectric permittivity values > 100,000 was obtained at lower frequency (10 Hz) and at higher temperatures (200 ºC) for La0.4Ba0.6Mn0.4Ti0.6O3 and La0.4Ba0.4Ca0.2Mn0.4Ti0.6O3 samples in dielectric measurement. At 1 kHz, the permittivity of La0.4Ba0.6Mn0.4Ti0.6O3 compound is ~ 20,000 at 0 ºC and slightly increases to ~ 54,000 at 125 ºC with low loss tangent ~ 0.8. While for La0.4Ba0.4Ca0.2Mn0.4Ti0.6O3 compound, the permittivity at 1 kHz is ~ 56,000 at 50 ºC and increase to ~ 97,000 at 100 ºC with the loss tangent ~ 0.7. For La0.4Ba0.2Ca0.4Mn0.4Ti0.6O3 and La0.4Ca0.6Mn0.4Ti0.6O3 samples, the values of dielectric permittivity are ~ 10,000 over three order of frequency magnitude and also show thermal stability. However, the permittivity at 1 MHz is within 100 to 200 for all samples. The high permittivity values at low frequency are due to the grain boundary effect whereas the low permittivity values at high frequency are attributes from the bulk effect. Doping with Sn ions decreases the magnitude of grain boundary permittivity at low frequencies and increases the loss factor. A Debye-like polarization behaviour with dc conduction are observed in the master plot. The relaxation peak and the dc conductivity in this titano-manganite compound were explained due to the trap-controlled hopping mechanism since the sample is dominated by electronic carriers. In traps phenomenon, delayed electronic transitions make a significant contribution to the complex dielectric permittivity. However, the decreases of the grain boundary magnitude at low frequency as the Sn ions increased resulting in the formation of anomalous low frequency dispersion (ALFD). In equivalent circuit modeling, the electrical property of the samples has been represented by a series combination of quasi-dc response, conductance and high frequency capacitance in parallel. The proposed model is in consistent with the outcome in complex impedance analysis and surface morphology observation consisting grains and grain boundaries. The conductivity of all samples obeys the empirical equations σ(ω) = σdc + Aωn. Each of the bulk and grain boundary response gives the shape of the empirical equation. The dc conductivity of the grain and grain boundary are fall in the range of semiconducting materials (~ 10-5 S/m to ~ 1 S/m from -100 ºC to 200 ºC). The analysis of conductivity reveals that the sample is p-type semiconductors with holes as the majority carriers. The increase of Sn ions increased the grain boundary conductivity causing overlapping with the bulk conductivity. The grain boundary region is more thermally activated than the bulk region where the activation energy of the grain boundary is in the range of 0.31 to 0.54 eV and 0.17 to 0.37 eV for the bulk. The activation energy obtained is consistent with an electron hopping mechanism.